2018
DOI: 10.1016/j.ebiom.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutation as Potential Negative Predictor for Response of Anti-CTLA-4 Therapy in Metastatic Melanoma

Abstract: TP53 has been proved to be associated with cytotoxic T-cell induced apoptosis, however, the association between TP53 and the benefit of immunotherapy in melanoma has not been studied. In the present study, we examined the relationship between TP53 mutation and response to CTLA-4 blockade in metastatic melanoma by analyzing the data from one public cohort consisting of 110 patients with metastatic melanoma. The sequencing, mRNA and survival data of 368 patients with skin melanoma from The Cancer Genome Atlas (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 24 publications
4
41
1
Order By: Relevance
“… In addition, lower clonotype and diversity were also present in patients with mutated TP53 (Supporting Information Fig. S9), which was reported recently to be a negative predictor for response to ICB treatment …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“… In addition, lower clonotype and diversity were also present in patients with mutated TP53 (Supporting Information Fig. S9), which was reported recently to be a negative predictor for response to ICB treatment …”
Section: Resultssupporting
confidence: 55%
“…S9), which was reported recently to be a negative predictor for response to ICB treatment. 36 Taken together, these findings indicate that the TCR repertoire is closely associated with several clinical characteristics, and high repertoire diversity reflects favorable immune status in patients with lung cancer, which may be exploited to direct anticancer treatment.…”
Section: Correlation Between the Tcr Repertoire And Clinical Charactementioning
confidence: 70%
“…The Friends and QuIP initiatives for TMB harmonization recommended to include as much relevant genetic and molecular information as possible in these panels, to avoid the need to re-biopsy the patient for further information. In line with this recommendation, we propose to also include in gene panels for TMB quantification other potential immunotherapy biomarkers but also negative predictors of immunotherapy response [69,70] and variants predisposing to adverse reaction to immunotherapy [71,72]. These and other recommendations which emerge from the studies reviewed here, including the one from the TMB Harmonization Working Group, are summed up in Additional file 6: Table S6.…”
Section: Future Perspectives and Recommendationsmentioning
confidence: 89%
“…In addition, Xiao et al studied in metastatic melanoma patients the relationship between TP53 mutation and the response to anti-CTLA-4 therapy. The authors reported that increased TP53 expression is significantly associated with poor response, poor progression-free survival, and poor overall survival, suggesting it as a negative predictor for response to CTLA-4 blockade [ 93 ].…”
Section: Tumor Mutational Burdenmentioning
confidence: 99%